A double design-science perspective of entrepreneurship – the example of smart contracts in the insurance market. Issue 1 (24th December 2020) - Hoffmann, Christian Hugo
Abstract : Purpose: Following the call for strengthening the third pillar of knowledge in entrepreneurship as well as work-applied management contexts constituted by pragmatic design principles, we present a case study on an insurtech for insurance firms specialized in smart contract insurance solutions such as flight delay or ski resort insurance. Design/methodology/approach: Design science. Findings: This not only serves as a pointer for how insurances may master their digital transformation while remaining competitive. But moreover, on the meta level, we find that the adoption of entrepreneurial design principles by the students, whose experiential project represents our case study, does not necessarily require continuous support or foundational knowledge to be delivered beforehand. However, for a deeper or more holistic assessment of the case sketched in their project, it makes sense to introduce them to newer developments such as the simple, practical framework of the Entrepreneur's Question Index. Originality/value: Innovative teaching method on innovative topics.